Implementasi Aktivitas Laboratorium Persekolahan Berorientasi Prinsip Merdeka Belajar Sebagai Upaya Penguatan Profil Pelajar Pancasila - Saulim DT Hutahaen; Theo Jhoni Hartanto; Suhartono (Jurnal Ilmiah Kanderang Tingang, 2023)
This research aims to support government programs in order to strengthen the principle of independent learning as an effort to increase the profile of Pancasila students through school laboratories. The optimal implementation of the Pancasila Student Profile must be supported by serious facilities and implementation as well as the support of all parties involved in it. One of the practicum activities can add to the learning experience, where students directly interact with various tools and materials to observe all the accompanying symptoms. Practicum can also be said to be an educational method for learning and practicing all activities in the practicum process in the laboratory, not only involving practical tools and materials, but also must be equipped with supporting facilities so that the practicum can run well and safely. Based on this, we provide books that can be used as basic guidelines and guides for students to carry out practical work in the laboratory. This activity is seen as having implications for character building or individual resilience of students or students. The Pancasila Student Profile has the main goal of maintaining the noble values ​​and morals of the nation, readiness to become a world citizen, realizing social justice, and achieving 21st Century competence. In our daily spirit and attitude in the community or profession, we must have a Pancasila student profile. Students defined here are superior human resources who are lifelong students who have global competence and behave in accordance with Pancasila values. The results of this research show that the implementation of the Pancasila student profile in schools is still less than optimal and the implications for the formation of student character are very strong. So if the Pancasila student profile is optimized in its implementation at school, a Pancasila student character will be formed. A good teacher is a teacher who performs well, but only in the classroom. They are able to improve their students' achievements, teach creatively and innovatively, and develop their own competencies. Meanwhile, the role of the Driving Teacher is not only limited to success in managing the class they teach. Apart from being a good teacher, a Driving Teacher must also have the will to lead, innovate, make changes. On this basis, Kejarcita exists to support teachers to become professional driving teachers.